Relined fiberglass posts: influence of resin opacity on the bond strength to intraradicular dentin - Maluly-Proni, Ana Teresa [UNESP]; Queiroz, Mariana Elias [UNESP]; Gomes, Matheus Henrique [UNESP]; Suzuki, Thaís Yumi Umeda; Reis, Bruna de Oliveira [UNESP]; Dos Santos, Paulo Henrique [UNESP] (FapUNIFESP (SciELO), 2024)
This study aimed to evaluate the bond strength between relined fiberglass posts with different composite resin opacities in different thirds of the intraradicular dentin. Thirty single-rooted premolars were endodontically treated and divided into three groups (n=10): fiberglass posts relined with translucent composite resin, fiberglass posts relined with opaque composite resin, and fiberglass posts without relining. After cementation of the posts, the specimens were cut perpendicular to the long axis of the tooth in slices of approximately 1.3 mm of each third to be analyzed (cervical, middle, and apical) and then subjected to the push-out test. The bond strength (MPa) data were subjected to Shapiro–Wilk normality tests and two-way repeated measures analysis of variance, considering the experimental groups and different regions as study factors. Tukey’s post-hoc test (p<.05) was applied for comparisons between the groups. In the cervical third, higher values of bond strength were found for the group relined with translucent resin, with a statistically significant difference for the other groups. In the other regions, both opaque and translucent resins showed similar results, but both showed higher values of bond strength compared to fiberglass posts without relining. The bond strength of fiberglass posts to different thirds of intraradicular dentin is influenced by composite resin relining as well as the opacity of the resin. The use of translucent composite resin is a more effective alternative for fiberglass posts relining.
Keywords: dentin; post and core technique; Resin cements